THE SECI MODEL IN ENHANCING EDUCATIONAL QUALITY THROUGH KNOWLEDGE MANAGEMENT - Andi Rifkah Afifah; Muh Nur Fuadi (Laboratorium Jurusan S1 Manajemen Pendidikan Islam, 2025)
This study aims to analyze the application of the SECI model in Knowledge Management (KM) to enhance educational quality at TPA-TQA Alluqmaniyyah Yogyakarta, a non-formal Islamic education institution. Employing a descriptive qualitative approach, this research explores the processes of knowledge socialization, externalization, combination, and internalization within this unique educational environment. Data were collected through in-depth interviews with institution leaders, observation of activities, and review of relevant documents and literature. The findings reveal that the implementation of the SECI model effectively facilitates the conversion of tacit knowledge into explicit forms through various practices, including student assessments, regular learning evaluations, curriculum documentation, and routine teacher training. The success of this implementation is significantly underpinned by robust collaboration among educators, the integral incorporation of Islamic values, and a pervasive reflective culture in decision-making processes. Although certain limitations persist, particularly concerning the aspect of digitalization, this knowledge management approach demonstrably proves effective in improving the overall educational quality at TPA-TQA Alluqmaniyyah.